Finite element analysis of a novel anatomical plate in posterolateral plateau fractures - Jian, Zhen; Jiang, Xinhua; Li, Dejian; Zhou, Jianhua; Yu, Baoqing; Yi, Chengqing (Frontiers in Surgery, 2024)
Objective: This study aims to analyze the biomechanical characteristics of posterolateral plateau fractures fixed by a novel anatomical plate using finite element analysis.: A three-dimensional digital model of the full length of right tibiofibula was obtained by CT scanning. A posterolateral tibial plateau fracture model was then created. The acquired fracture model was assembled with 4 groups of internal fixations: Group A, novel anatomical plate; Group B, straight buttress plate; Group C, oblique T-shaped locking plate; Group D, two lag screws. Axial loads of 500, 1000 and 1500 N perpendicular to the horizontal plane were used to simulate the stress on the lateral plateau of a 65kg person standing, walking and fast running. Results: Vertical displacements of the posterolateral fragments in each of the four groups gradually increased under loads from 500 N to 1500 N. The maximum displacement of the fracture fragment in four groups were all located on the lateral side of the proximal part, and the displacement gradually decreased from the proximal part to the distal end. The maximum displacement values under the axial load of 1500 N was in the following order: novel 删除了: Newly Modified